The Relationship between Parental Involvement and Studentsâ English Achievement at 8th Grade Students in SMP Negeri 1 Singaraja - Artasthana, G. A.; Marhaeni, A. A. I. N. (Journal of Psychology and Instructions, 2017)
The purpose of this study is to investigate the significant relationship between parental involvement and studentsâ English achievement of 8th grade students in SMP Negeri 1 Singaraja. The design of this study is simple correlation involving 58 students and their parents as the sample. The material of the questionnaire was adopted from Shute et al. (2011) and was used to collect the data of the home â based parental involvement, while the data of the English achievement was collected from school principal. Pearson Product Moment Correlation was used to investigate the correlation between parental involvement and studentsâ English achievement. The result shows that parental involvement and studentsâ English achievement have a positive and significant correlation, with the Pearson Correlation value = 0.440 > 0.05.